THE EFFECT OF PRODUCT QUALITY, PRICE AND SERVICE QUALITY ON CONSUMER SATISFACTION AT CAFE SAVA KOFFIE - Marselina, Sherli; Badri, Juarsa (Bina Bangsa International Journal of Business and Management, 2022)
This study examines the effect of product quality, price and service quality on customer satisfaction at Café Sava Koffie. This type of research is quantitative, the research process emphasizes objective measurement of results using statistical analysis. The population in this study are consumers who visit Café Sava Koffie. The total population is 606 people. The sampling technique used is accidental sampling based on certain criteria, namely consumers who visit Café Sava Koffie, while the number of samples is 86 people obtained using the slovin formula. The type of data used in this study is quantitative data. While the data sources are primary and secondary. The data analysis technique uses multiple linear regression using the SPSS version 21.00 program. The hypothesis was tested using the t test at = 0.05. This study indicates that product quality, price, and service quality have a positive and significant effect on consumer satisfaction at Café Sava Koffie